Statement made by Jane Tolmach to the Members of the Board of Supervisors June, 1999 - Jane Tolmach:::::: (1999)
A statement made by Jane Tolmach requesting that all documents be reviewed again and for the cost of the FAA's investment in the airport be divided into a year-by-year basis.